2013
DOI: 10.1021/nn401562f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure of RADA16-I Designer Self-Assembling Peptide Nanofibers

Abstract: The designer self-assembling peptide RADA16-I forms nanofiber matrices which have shown great promise for regenerative medicine and 3-dimensional cell culture. RADA16-I has a β-strand-promoting alternating hydrophobic/charged motif, but arrangement of β-strands into the nanofiber structure has not been previously determined. Here we present a structural model of RADA16-I nanofibers, based on solid-state NMR measurements on samples with different schemes for 13C isotopic labeling. NMR peak positions and line wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
144
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(153 citation statements)
references
References 59 publications
9
144
0
Order By: Relevance
“…Ribbon-like nanofibers were observed in both solutions of RADA 16-IKVAV and RADA 16-RGD, which were similar to the RADA 16-I morphology investigated by Cormier et al 30 . As documented previously, the rod-like RADA 16-I molecule and those after modification assemble into a stable β-sheet double-tape structure 6 , which then associated into ribbons 31 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Ribbon-like nanofibers were observed in both solutions of RADA 16-IKVAV and RADA 16-RGD, which were similar to the RADA 16-I morphology investigated by Cormier et al 30 . As documented previously, the rod-like RADA 16-I molecule and those after modification assemble into a stable β-sheet double-tape structure 6 , which then associated into ribbons 31 .…”
Section: Resultssupporting
confidence: 86%
“…whereas RADA16-RGD fell out of its theoretical diameter 21 , which suggested the lateral association of multiple subunits 30 . A nanofiber network was observed in -IKVAV-RGD hydrogel.…”
Section: Resultsmentioning
confidence: 92%
“…Amyloid fibrils formed in vitro are generally polymorphic unless special fibril growth protocols are used, such as repeated seeding (8) or long periods of incubation with agitation to promote convergence to a single structure with lowest free energy (35). Prior solid-state NMR studies of the gel-forming peptides RADA16-I and MAX8 suggested polymorphism or incomplete molecular structural order within the hydrogels (14,20).…”
Section: Discussionmentioning
confidence: 99%
“…Disease-associated amyloid and prion fibrils are known to be polymorphic at the molecular structural level (7,8,12,13), implying that structures within peptide and protein fibrils are generally not determined uniquely by amino acid sequences and do not necessarily represent thermodynamic ground states. A model for fibrils formed by the designed peptide RADA16-I has been proposed by Cormier et al based on solidstate NMR data (14), in which RADA16-I monomers form single β-strands within a double-layered cross-β structure. Solidstate NMR spectra of this hydrogel-forming peptide also indicate coexistence of several distinct fibril structures, suggesting that polymorphism may also be a trait of designed sequences.…”
mentioning
confidence: 99%
“…These peptides (typically 816 amino acids long) assemble in water to form -sheet rich fibers that, when above the critical gelation concentration (CGC), entangle and/or associate/aggregate to form a 3-D percolated, nanofibrillar network that traps water (i.e., a hydrogel). Examples of SAPHs exploiting Zhangs peptide design include: RADA (14), KLD (15), FKE (16,17), and Q11 (18), among many others. These SAPHs provide a flexible platform for cell culture, as the properties (mechanical and functional) can be tailored by simply altering the peptide concentration, formulation, and amino acid sequence (19,20).…”
mentioning
confidence: 99%